Tanggung Jawab Notaris Terhadap Surat Keterangan Waris Tanpa Mencantumkan Salah Satu Ahli Waris dalam Pandangan Hukum Perdata - Anton Sujarwo Dunggio; Nirwan Junus; Mohamad Taufik Zulfikar Sarson (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
This study aims to ensure that heirs cannot be simply removed or not handed over to heirs who have rights. Because there are two types of heirs, this is regulated by the Civil Code, namely heirs based on marriage and descent, and heirs determined through a will. This study applies a normative approach, which focuses on literature studies in the field of law. Normative legal research examines legal behavioral products, such as laws, through normative case studies.